Pemanfaatan Bacillus thuringiensis dan Kompos Trichoderma sp. untuk Mengendalikan Hama dan Penyakit Utama Tanaman Kubis (Brassica oleraceae L.) di Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan - YASA, I KETUT PURNA; WIRYA, GUSTI NGURAH ALIT SUSANTA; UTAMA, MADE SUPARTHA; SUDIARTA, I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
The utilization of Bacillus thuringiensis and Compost Plus Trichoderma sp  to Control the Key Pests and Diseases of  Cabbage ( Brassica oleraceae ) in Bangli Village Baturiti District, Tabanan Regency.  The experimental design was used Factorial Randomize Complete Blok Design, with two  factors: Factor I : (A) Seedling of Trichoderma sp., Soil containing compost and Trichoderma sp., (B) Seedling of Trichoderma sp., Soil containing compost but without Trichoderma sp., (C) Cow manure and spice extracts bali. Factor II : (a) B. thuringiensis and (b) Without B. thuringiensis . The results treatment of seedling with Trichoderma sp., Soil containing compost and Trichoderma sp. showed the lowest percentage of the disease (32.5%), and disease severity (19.37%) if compare with other treatments. On the order hand B. thuringiensis was effect to the population of C. binotalis and total of cabbage production. The population of C. binotalis was lower on cabbage with BT treatment (2,33) if compare without BT treatment (9,65 ). Treatment of seedling with Trichoderma sp., Soil containing compost and Trichoderma sp. showed the highest total yield (16 kg/plot), as well as the treatment of B. thuringiensis was highest total of yield  (16.20 kg/plot).